Early life lessons: The lasting effects of germline epigenetic information on organismal development - Carolina Galan; Marina Krykbaeva; Oliver J. Rando (Elsevier, 2020)
Background: An organism's metabolic phenotype is primarily affected by its genotype, its lifestyle, and the nutritional composition of its food supply. In addition, it is now clear from studies in many different species that ancestral environments can also modulate metabolism in at least one to two generations of offspring. Scope of review: We limit ourselves here to paternal effects in mammals, primarily focusing on studies performed in inbred rodent models. Although hundreds of studies link paternal diets and offspring metabolism, the mechanistic basis by which epigenetic information in sperm programs nutrient handling in the next generation remains mysterious. Our goal in this review is to provide a brief overview of paternal effect paradigms and the germline epigenome. We then pivot to exploring one key mystery in this literature: how do epigenetic changes in sperm, most of which are likely to act transiently in the early embryo, ultimately direct a long-lasting physiological response in offspring? Major conclusions: Several potential mechanisms exist by which transient epigenetic modifications, such as small RNAs or methylation states erased shortly after fertilization, could be transferred to more durable heritable information. A detailed mechanistic understanding of this process will provide deep insights into early development, and could be of great relevance for human health and disease.